Metal 3D printing of biometals for prostheses and implants: a review - Apurba Das; Pradhyut Rajkumar (Exploration of BioMat-X)
Metal 3D printing has revolutionized the fabrication of biometallic prostheses and implants, offering unprecedented design flexibility, patient-specific customization, and enhanced biomechanical performance. This review explores the current advancements in metal additive manufacturing (AM) techniques, including selective laser melting (SLM), electron beam melting (EBM), fused deposition modeling (FDM), directed energy deposition (DED), sheet lamination, stereolithography (SLA), and binder jetting, for processing biocompatible metals such as titanium, cobalt-chromium, and stainless steel. The article discusses major benefits, such as enhanced osseointegration, complex lattice architectures for weight saving, and optimized mechanical properties. The challenges of residual stresses, surface finish, and regulatory issues are also discussed. The review concludes by defining future research avenues in material design, process development, and clinical translation to increase the efficacy and reliability of 3D-printed biometal implants.